IgE-mediated soy protein sensitization in children with cow’s milk allergy - Agustina Santi (Paediatrica Indonesiana, 2012)
Background Soy-based formula as an alternative to cow's milk formula is preferable to extensively hydrolyzed protein formula because of the lower cost and more acceptable taste. However, cow's milk allergy patients can subsequently develop a sensitivity to soy protein. Objective To compare soy protein sensitization in children with and without an allergy to cow's milk. Methods This study was conducted in Yogyakarta from September 2007 until March 2008. Subjects were children aged below 4 years with an atopic history. Subjects were divided into 2 groups: those with a positive skin prick test to cow's milk and those with a negative skin prick test to cow's milk (control group). Both groups were given soy formula and tested at 6 weeks for sensitization to soy. Results There were 45 children in each group. Age, sex, and atopic history were similar in both groups. We found no soy protein sensitization (negative skin prick results) in all subjects from both groups. Conclusion Risk of immunoglobulin E-mediated sensitization to soy protein was not proven in children with cow's milk allergy. [Paediatr lndones. 2012;52:67-71).